Co(III)salen Catalyzed Enantioselective C3‐Indolylation of Spiro‐Epoxyoxindoles and Its Mechanistic Studies. Issue 23 (16th October 2020) - Hajra, Saumen; Roy, Sayan; Mondal, Ananda Shankar
Abstract: Catalytic asymmetric C3‐indolylation of N ‐protected spiro‐epoxyoxindoles has been developed for the access of 3‐(3‐indolyl)‐oxindole methanols with excellent enantioselectivity (ee up to >99%). The widespread substrate scope and easily accessible Co(III)‐salen over 1, 1′‐Spirobiindane‐7, 7′‐diol phosphoric acid prove our condition to be more beneficial than the chiral Brø nsted acid‐catalyzed reaction. Further, kinetic resolution of spiro‐epoxides is achieved in high enantiomeric excess under certain conditions. The detailed mechanistic study endorses that the feedback inhibition played a key role which restricts the dynamic kinetic resolution process. Besides it also revealed the SN 2′ mechanism for the Co(III)‐salen catalysed C3‐indolylation of spiro‐epoxyoxindoles. Abstract :